2015
DOI: 10.1007/s11243-015-9959-5
|View full text |Cite
|
Sign up to set email alerts
|

A palladium–phosphine catalytic system as an active and recycable precatalyst for Suzuki coupling in water

Abstract: The Suzuki-Miyaura reaction of various aryl halides with aryl boronic acids using {[Ph 2 PCH 2 PPh 2-CH=C(O)(C 10 H 7 )]PdCl 2 } as a catalyst has been investigated. The X-ray crystal structure of the catalyst reveals a five-membered chelate ring formed by coordination of the ligand through the phosphine group and the ylidic carbon atom to the metal center. This palladacycle exhibited excellent activities and reusability in the aqueous phase for the Suzuki cross-coupling reactions of arylboronic acids with ary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…The dihedral angle between the keto group and the cyano‐substituted aromatic ring is 16.1(2)°. The structure is similar to that of other Pd ylide complexes, such as dichloro‐(1‐(((diphenylphosphino)methyl)(diphenyl)phosphonio)‐2‐(2‐naphthyl)‐2‐oxoethyl)palladium(II) and (2‐(biphenyl‐4‐yl)‐1‐(((diphenylphosphino)methyl)(diphenyl)phosphonio)‐2‐oxoethyl)(dichloro)palladium …”
Section: Resultssupporting
confidence: 66%
“…The dihedral angle between the keto group and the cyano‐substituted aromatic ring is 16.1(2)°. The structure is similar to that of other Pd ylide complexes, such as dichloro‐(1‐(((diphenylphosphino)methyl)(diphenyl)phosphonio)‐2‐(2‐naphthyl)‐2‐oxoethyl)palladium(II) and (2‐(biphenyl‐4‐yl)‐1‐(((diphenylphosphino)methyl)(diphenyl)phosphonio)‐2‐oxoethyl)(dichloro)palladium …”
Section: Resultssupporting
confidence: 66%
“…[22] In a very recent study, Khazalpour and co-workers reported the palladium-phosphine system 7 as an active and recyclable pre-catalyst for SMC in water. [23] A fivemembered chelate ring is formed upon coordination of the ligand through the phosphine and the ylidic carbon atom. The catalytic system could be reused four times without significant loss of activity (Scheme 7).…”
Section: Methodsmentioning
confidence: 99%
“…Pt(I) and Pt(III) complexes are noted for instability and any reduction or oxidation processes centralized on metal orbitals of Pt(II) complexes typically exhibit irreversible behavior . In 4 , such as 3 , peak C 4 (− 0.77 V) is assigned to the two electron reduction of Pd(II) center in the complex and the second reduction peak, C Y2 (− 0.49 V), is related to the reduction of ylide Y 2 (Figure , curve d) . The overall two‐electron reduction of the Pd(II) complexes is expected to take place in separate one‐electron steps and this might be achieved via manipulation of the thermodynamics or electrode kinetics of either step by correct choice of the experimental conditions.…”
Section: Resultsmentioning
confidence: 99%